2020
DOI: 10.15294/spnj.v2i2.39761
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Gizi, Asupan Makanan dengan Status Gizi Siswi Mts Darul Ulum

Abstract: Pengetahuan gizi merupakan landasan perilaku gizi seseorang, yang akan berefek pada asupan makanan dan status gizi siswi. Tujuan penelitian ialah mengetahui hubungan pengetahuan gizi dan asupan makanan dengan status gizi. Jenis penelitian adalah deskriptif dengan desain cross sectional. Subjek penelitian ini sebanyak  51 siswi Mts Darul Ulum kelas 8 dan 9. Penelitian dilakukan bulan September 2019-Februari  2020. Uji hubungan menggunakan uji  Pearson dan uji Sperman’s rho. Uji korelasi pengetahuan gizi dan asu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
3
8
0
16
Order By: Relevance
“…This study is in accordance with the previous, where if a food is cooked with an improper diet, it causes the emergence of bacteria that can endanger public health [4]. If this is done continuously, it can make people unable to pay attention to their diet by applying a form of nutritional content as a guideline or feeding rules regarding nutritional knowledge as the basis for one's nutritional intake behavior [5]. Processing food must be appropriate because of the vulnerability of chicken meat to the dangers of microbes that contaminate chicken meat, namely salmonella [6].…”
Section: Introductionsupporting
confidence: 85%
“…This study is in accordance with the previous, where if a food is cooked with an improper diet, it causes the emergence of bacteria that can endanger public health [4]. If this is done continuously, it can make people unable to pay attention to their diet by applying a form of nutritional content as a guideline or feeding rules regarding nutritional knowledge as the basis for one's nutritional intake behavior [5]. Processing food must be appropriate because of the vulnerability of chicken meat to the dangers of microbes that contaminate chicken meat, namely salmonella [6].…”
Section: Introductionsupporting
confidence: 85%
“…The findings of the data above can indicate a lack of knowledge regarding food sources of fat, which can have an impact on unwittingly excess fat intake. Research by Lestari in 2020 [37] found a significant relationship between nutritional knowledge and fat intake, where knowledge related to fat sources would affect food choices and impact nutritional intake consumed by adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…KEK yang dialami responden dapat disebabkan kurangnya pengetahuan tentang gizi sehingga mempengaruhi perilakunya dalam memilih makanan untuk memenuhi kebutuhan nutrisinya. Pengetahuan giziadalah pengetahuan terkait makanan dan zat gizi, sumber-sumber zat gizi pada makanan,makanan aman di konsumsi sehingga tidak menimbulkan penyakit dan cara mengolah makanan yang baik agar zat gizi dalam makanan tidak hilang serta bagaimana hidup sehat [12].…”
Section: B Kejadian Kek Pada Ibu Hamil DI Desa Bunder Daerah Pesisirunclassified